CHARACTER ANALYSIS OF JACE WAYLAND IN THE MORTAL INSTRUMENTS: CITY OF BONES NOVEL THROUGH HIERARCHY OF HUMAN NEEDS THEORY OF ABRAHAM MASLOW - Latifah, Siti Noor; Kuncara, Singgih Daru; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
ABSTRACTThe objective of this research was to show the process of Jace, the character in The Mortal Instruments: City of Bones novel, in fulfilling his need through Abraham Maslow’s theory about hierarchy of human needs and to describe about his character based on his need. This data used descriptive qualitative research because the data were found in the form of dialogue and narration that will explained about the character. The researcher used The Mortal Instruments: City of Bones novel as the source data. The steps of data collection were reading the novel The Mortal Instruments: City of Bones and understanding about the dialogue and narration that had been shown, then identified the data based on the theory of human needs. Last, the data were arranged based on the research questions. From the finding of this analysis, Jace had fulfilled four needs of human needs by Abraham Maslow. They are physiological need, safety need, love and belongingness need, and esteem need. Meanwhile Jace could not fulfill the last need of self-actualization need because there are some characteristic that he could not get. They are clear perception or reality, acceptance, problem centered, humility and respect, and sense of humor. From analysis based on his needs, it was found that he showed many characters through the needs that he had fulfilled. Keywords: hierarchy of human needs, character, The Mortal Instruments: City of Bones novel ABSTRAKTujuan dari analisis ini adalah untuk memperlihatkan proses Jace, karakter dalam novel The Mortal Instruments: City of Bones, dalam memenuhi kebutuhannya melalui teori Abraham Maslow tentang tingkatan kebutuhan-kebutuhan manusia dan menjelaskan tentang karakternya berdasarkan kebutuhannya. Analisis ini menggunakan metode penelitian deskriptif kualitatif karena data ditemukan dalam bentuk dialog dan narasi yang akan menjelaskan tentang karakter. Peneliti menggunakan novel The Mortal Instruments: City of Bones sebagai sumber data. Langkah-langkah dalam pengumpulan data adalah membaca novel The Mortal Instruments: City of Bones dan memahami tentang dialog dan narasi yang telah diperlihatkan, kemudian mengidentifikasi data berdasarkan teori kebutuhan-kebutuhan manusia. Terakhir data disusun berdasarkan pertanyaan dari penelitian. Dari analisis ini, Jace telah berhasil memenuhi empat kebutuhan dari kebutuhan-kebutuhan manusia yang dijelaskan oleh Abraham Maslow. Diantaranya kebutuhan fisiologi, kebutuhan akan rasa aman, kebutuhan akan rasa sayang dan memiliki, dan kebutuhan penghargaan. Sementara itu, Jace tidak bisa memenuhi kebutuhan terakhir yaitu kebutuhan aktualisasi diri karena ada beberapa karakteristik dari kebutuhan tersebut yang tidak bisa dipenuhi. Diantaranya pemikiran yang jelas atau kenyataan, penerimaan, pemecah masalah, rendah hati dan menghormati, dan memiliki rasa humor. Dari analisi berdasarkan kebutuhan-kebutuhan Jace, ditemukan bahwa Jace memperlihatkan banyak karakter melalui kebutuhan-kebutuhan yang sudah terpenuhi. Kata kunci: hierarki kebutuhan manusia, karakter, novel The Mortal Instruments: City of Bones